On the interaction between weed and bird damage in rice - Demont, M.; Rodenburg, J. (Wiley, 2016)
Weeds and granivorous birds are the two major biotic constraints to rice production in sub‐Saharan Africa. Anecdotal evidence advances the hypothesis that weedy fields attract granivorous birds to the extent that the joint weed × bird impact on crops is synergistic. We develop a theoretical model, based on experimental data, of the interaction between weed and bird damage to formally test this hypothesis. We observe that the response of bird‐inflicted yield loss to weeds is unimodal and inverse‐U‐shaped. Bird‐inflicted yield loss increases from 44% in weed‐free conditions to a maximum of 55% at a critical weed infestation level of 20 g dry weight m−2. We conclude that the 11% increase in yield loss can be attributed to the synergistic interaction between weed and bird damage in rice. Our theory provides new insights into the analysis of the interaction between weeds and pests in general and supports a revision of currently accepted recommendations for weed management in rice. In areas where birds constitute an important production risk, it would be beneficial for rice farmers to remove those weeds that are tall enough to attract birds, even beyond the critical weed period.